PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP STRES KERJA PADA PEGAWAI KANTOR KECAMATAN PADANG TIMUR - Zulmaidarleni Zulmaidarleni; Rini Sarianti; Yuki Fitria (Jurnal Ecogen, 2019)
This study aims to prove and analyze the effect of workload and physical work environment on work stresson study the sampling method used was total sampling considering the number of samples used was less than 100 people. The analytical method used to prove the hypothesis is to use multiple regression models and t-statistical testing. Based on the results of testing the hypothesis it was found that the first workload had a positive and significant effect on work stress on employees of the Padang Timur Sub-District Office, while the second hypothesis was successfully proven the work environment had a negative and significant effect on the work stress of employees of the East Padang District Office.Keyword: Beban Kerja, Lingkungan Kerja Fisik, Stres Kerja